2020
DOI: 10.1021/acs.organomet.9b00749
|View full text |Cite
|
Sign up to set email alerts
|

Diorganyl Dichalcogenides as Surface Capping Ligands for Germanium Nanocrystals

Abstract: Indirect ligand exchange methods have been demonstrated to replace the oleylamine capping with dodecanethiol for germanium nanocrystals (Ge NCs). In these methods, hydrazine is employed to effectively remove the oleylamine ligand before the NCs are passivated by microwave-assisted heating with dodecanethiol. In this work, octadecanethiol passivation is accomplished by the in situ reaction of dioctadecyl disulfide with diphenylphosphine. 1H NMR and FTIR are used to characterize the surface ligand capping and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…1 H and 31 P NMR were performed on OAm/TOP and DDT-capped Sb-doped Ge NCs (Figures , ). The absence of a vinylic proton peak between 5 and 6 ppm indicates the complete removal of OAm ligands through hydrazine treatment. , Recently, we reported a detailed solution NMR study on OAm-capped Ge NCs synthesized at different temperatures to determine the binding mode of this native primary amine on the Ge surface . Two distinct fractions of both weakly physisorbed and strongly covalent X-type bonded OAm on the Ge surface were resolved by exchange reactions with different functional groups (amines/ammonium, thiols, and carboxylic acids).…”
Section: Resultsmentioning
confidence: 99%
“…1 H and 31 P NMR were performed on OAm/TOP and DDT-capped Sb-doped Ge NCs (Figures , ). The absence of a vinylic proton peak between 5 and 6 ppm indicates the complete removal of OAm ligands through hydrazine treatment. , Recently, we reported a detailed solution NMR study on OAm-capped Ge NCs synthesized at different temperatures to determine the binding mode of this native primary amine on the Ge surface . Two distinct fractions of both weakly physisorbed and strongly covalent X-type bonded OAm on the Ge surface were resolved by exchange reactions with different functional groups (amines/ammonium, thiols, and carboxylic acids).…”
Section: Resultsmentioning
confidence: 99%
“…Ge 1– x Sn x NCs were synthesized via the microwave-assisted reduction of equal molar amounts of GeI 2 and bis­[bis­(trimethylsilyl)­amino]­tin­(II) in OAm at temperatures from 210 to 280 °C. The resulting OAm-capped Ge 1– x Sn x NCs were treated with hydrazine to remove the OAm ligand and repassivated with DDT using microwave-assisted heating. , PXRD patterns of the OAm-capped Ge 1– x Sn x NCs prepared at the various temperatures, along with the corresponding DDT-capped Ge 1– x Sn x NCs, are shown in Figure . The patterns show that the indicated cubic Ge peaks are shifted from the expected positions to lower angles due to the incorporation of Sn in the structure, consistent with a cubic Ge 1– x Sn x alloy structure.…”
Section: Results and Discussionmentioning
confidence: 99%
“…For Ge 1– x Sn x NCs, direct ligand exchange methods have been demonstrated to result in a partial replacement of the OAm ligand for films and solutions of NCs, and it has been shown that Ge 1– x Sn x NCs can be protected with a CdS shell or a thin coating of GeS . In this work, a hydrazine-assisted ligand exchange method, previoulsy applied to Ge- and Bi-doped Ge NCs, is used to achieve thiol passivation of Ge 1– x Sn x NCs synthesized at a range of temperatures. ,, Following ligand exchange, the local structure of GeSn NCs was characterized by extended X-ray absorption fine structure (EXAFS). EXAFS can probe the local environment about alloy or dopant atoms in the structure of metastable nanomaterials.…”
Section: Introductionmentioning
confidence: 99%
“…Many inhomogeneities, defects, and structural or elemental artifacts can offer sites for recombination, including vacancies, grain boundaries, and interfaces. The combination of these recombination centers at the nanoscale are referred to as surface trap states (STSs). …”
Section: Photoluminescencementioning
confidence: 99%
“…One of the most common ways of reducing or eliminating STSs is the use of ligands as capping agents. ,,,, The tendency of Ge to oxidize can be ameliorated or suppressed by shielding the NP surface with a layer of molecules, which in the case of good coverage can prevent exposure of the Ge surface to oxygen and passivate reactive dangling bonds. Ligands are often already introduced during synthesis, where they are simultaneously used as the solvent, and to mediate growth and control the resulting NP morphology.…”
Section: Surface Chemistrymentioning
confidence: 99%